Antibiotic Persistence Of Esherichia Coliin High And Low Nutrient Conditions - ULFAT I. BAIG,; SHAGUFTA I. SHAIKH,; TASNEEM Q. RAMPURWALA, (International Journal of Pharma and Bio Sciences, 2012)
Aging in unicellular organisms and is presumably due to asymmetric distribution of damaged proteins and other components during cell division. The asymmetry-induced aging is inevitable or an adaptive response is debated. Minimum inhibitory concentration results were expected to show that the low cultures adapted to oligotrophic nutrient medium would be highly sensitive to the different antibiotic concentrations since there is a cost involved in carrying the antibiotic genes, but instead the results showed that the cell cultures grown in low nutrient media were resistant to the antibiotic and had a higher growth rate which indicated that there was no cost involved. The, results suggest that cellular aging due to asymmetric division may shows plasticity as well as evolvability in response to the nutritional environment.